Aliran Rasionalisme Filsuf Abad Modern (Rene Descartes) - Amalia Febri Yanti; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the review of one of the philosophers in the early modern age of rationalism, namely Rene Descartes. This research method applies a qualitative type through library studies and content analysis. The results and discussion regarding the stages of the workings of the doubt method developed by Rene Descartes, innate ideas, the existence of God and criticism of the flow of rationalism developed by Rene Descartes. The conclusion of this study is to get to know one of the philosophers at the beginning of the modern age of rationalism, namely Rene Descartes who has a very solid philosophical foundation and certainty that has clear criteria so that it is difficult to doubt its validity.